Reversal of acute kidney injury after peritoneal dialysis in a dog: a case report - Guimaraes-Okamoto, P. T. C. [UNESP]; Geraldes, S. S. [UNESP]; Ribeiro, J. F. A. [UNESP]; Vieira, A. N. L. S. [UNESP]; Porto, L. P. [UNESP]; Barretti, P. [UNESP]; Lourenco, M. L. G. [UNESP]; Melchert, A. [UNESP] (Czech Academy Agricultural Sciences, 2016)
Acute kidney injury is characterised by a sudden injury to the renal parenchyma and causes defects in its excretory, metabolic and endocrine function. Dialysis therapy has been instituted in small animal clinics with the aim of removing the metabolic waste and correcting the electrolyte disturbances stemming from renal dysfunction. Peritoneal dialysis is a therapy based on the use of the peritoneum as a semipermeable membrane through which solutes and fluids are exchanged between blood from the peritoneal capillaries and the dialysis solution. This report describes a case of acute kidney injury stemming from drug therapy in a 13-year-old female mongrel canine. The patient exhibited anorexia, emesis, prostration and anuria and had a history of prolonged treatment with meloxicam. The patient also presented with azotaemia and metabolic acidosis. When anuria continued to persist after drug therapy (volume restoration, chemical and osmotic diuresis and renal vasodilation), peritoneal dialysis was instituted. Three cycles of peritoneal dialysis were performed; during the second cycle, the patient's anuria was reversed, and at the end of the third cycle she showed a significant reduction in azotaemia, hyperkalaemia and an improved metabolic acidosis. Therefore, peritoneal dialysis showed satisfactory clinical results and reversed anuria, reduced azotaemia and electrolyte disturbances, thereby providing clinical improvement.
Keywords: dialysis therapy; small animals; renal dysfunction; acute kidney injury; blood gases; electrolytes; anuria